2018
DOI: 10.3390/m1009
|View full text |Cite
|
Sign up to set email alerts
|

2-{[(4-Hydroxy-3,5-dimethoxyphenyl)methylidene]hydrazinylidene}-4-oxo-1,3-thiazolidin-5-yl Acetic Acid

Abstract: Thia-Michael addition of 2-[(4-hydroxy-3,5-dimethoxyphenyl)methylidene]hydrazine-1-carbothioamide (1) with maleic anhydride results in the formation of the title compound 2-{[(4-hydroxy-3,5-dimethoxyphenyl)methylidene]hydrazinylidene}-4-oxo-1,3-thiazolidin-5-yl acetic acid 2. The precursor 1 is synthesized by the reaction of 4-hydroxy-3,5-dimethoxybenzaldehyde and thiosemicarbazide in the presence of glacial acetic acid as the catalyst. The structure of the title compound is determined by elemental analysis, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…Again, the formation of the hydrogen bond between the C=O group and Ser228 was observed. Thus, the obtained results support previous data [ 69 , 70 , 71 , 72 ] that MurB maybe is the most appropriate target for the antibacterial activity for this chemical series.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Again, the formation of the hydrogen bond between the C=O group and Ser228 was observed. Thus, the obtained results support previous data [ 69 , 70 , 71 , 72 ] that MurB maybe is the most appropriate target for the antibacterial activity for this chemical series.…”
Section: Resultssupporting
confidence: 89%
“…It was found that benzothiazole derivatives are mentioned as Gyrase inhibitors [ 66 , 67 , 68 ]. On the other hand, according to the literature, thiazolidinones act as MurB inhibitors [ 69 , 70 , 71 , 72 ]. Furthermore, prediction of the mechanism of action by computer program PASS indicated Thymidylate kinase as the probable antibacterial target.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation